Prefrontoparietal dysfunction during emotion regulation in anxiety disorder: a meta-analysis of functional magnetic resonance imaging studies - Wang HY (Dove Medical Press, 2018)
Hai-Yang Wang,1 Xiao-Xia Zhang,1 Cui-Ping Si,1 Yang Xu,1 Qian Liu,1 He-Tao Bian,1 Bing-Wei Zhang,2 Xue-Lin Li,3 Zhong-Rui Yan1 1Department of Neurology, Jining No 1 People’s Hospital, Jining, Shandong Province, China; 2Department of Neurology and Psychiatry, First Affiliate Hospital of Dalian Medical University, Dalian, Liaoning Province, China; 3Department of Intensive Care Unit, Jining No 1 People’s Hospital, Jining, Shandong Province, China Objective: Impairments in emotion regulation, and more specifically in cognitive reappraisal, are thought to play a key role in the pathogenesis of anxiety disorders. However, the available evidence on such deficits is inconsistent. To further illustrate the neurobiological underpinnings of anxiety disorder, the present meta-analysis summarizes functional magnetic resonance imaging (fMRI) findings for cognitive reappraisal tasks and investigates related brain areas.Methods: We performed a comprehensive series of meta-analyses of cognitive reappraisal fMRI studies contrasting patients with anxiety disorder with healthy control (HC) subjects, employing an anisotropic effect-size signed differential mapping approach. We also conducted a subgroup analysis of medication status, anxiety disorder subtype, data-processing software, and MRI field strengths. Meta-regression was used to explore the effects of demographics and clinical characteristics. Eight studies, with 11 datasets including 219 patients with anxiety disorder and 227 HC, were identified.Results: Compared with HC, patients with anxiety disorder showed relatively decreased activation of the bilateral dorsomedial prefrontal cortex (dmPFC), bilateral dorsal anterior cingulate cortex (dACC), bilateral supplementary motor area (SMA), left ventromedial prefrontal cortex (vmPFC), bilateral parietal cortex, and left fusiform gyrus during cognitive reappraisal. The subgroup analysis, jackknife sensitivity analysis, heterogeneity analysis, and Egger’s tests further confirmed these findings. Conclusions: Impaired cognitive reappraisal in anxiety disorder may be the consequence of hypo-activation of the prefrontoparietal network, consistent with insufficient top-down control. Our findings provide robust evidence that functional impairment in prefrontoparietal neuronal circuits may have a significant role in the pathogenesis of anxiety disorder. Keywords: anxiety disorder, emotion regulation, cognitive reappraisal, fMRI, prefrontoparietal network, signed differential mapping